Studing the effect of aqueous extract of the Persian Gulf carpet anemone (Stichodactyla haddoni) on breast cancer cell line in vitro - Z. Moghadasi; Sh. Jamiliorcid ; D. Shahbazzadeh; N. Mossafa; K. Poshang bagheri (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
Numerous proteins, peptides, and chemical agents in the venom of venomous marine animals are biological active molecules with beneficial pharmacological properties. The main goal of this research was to study the cytotoxic effects of the isolated crude venom from the Persian Gulf sea anemone, Stichodactyla haddoni against Breast (MD-MBA231), and Human embryonic kidney (HEK-293) cell lines in vitro through using MTT assay. Samples of S. haddoni were collected from coastal waters of Lark Island in the Persian Gulf at the south of Iran. Extraction of aqueous part from tentacle was performed. The cell line was cultured in complete tissue culture medium. These cells were exposed to different concentration of venom extract through serial dilution of 100, 50, 25, 12.5, 6.25, 3.125, 1.56, 0.78 μg/ml (ratio 1/2) in 24 hour time duration. The results of kruskal-wallis test indicated that the cytotoxic activity of crude venom extract on cell lines were similar in almost all concentrations and significant differences were not observed (p>0.05). IC50 of crude venom extract against breast (MD-MBA231) and normal (HEK-293) cell lines was observed at 4.13, 117.8µg/ml, respectively. Results obtained from this study showed that increasing the concentration of extract led to the increasing death of both cell lines. Comparing the percentage of death between two cell lines at different concentrations indicated that aqueous extract induced approximately 3.16 folds more cell toxicity on cancer cell line rather than on normal cell lines. Therefore, crude venom extract of S. haddoni can be considered as a strong preventive agent for growth reduction of cancer cell lines especially for breast cancer cell line with low toxicity on normal human cells.